Local media : expansion of radio and political accountability : evidence from Colombia (2015)
Access to more information by a group of voters may represent more knowledge about the political system and incentivize people to make better choices. In this paper I argue that mass media have an impact over voters' knowledge, reflected on one of the main forms of political participation that citizens have in a democracy: voting and politicians' performance. The media outlet I take into account is radio, starting from its last stage of expansion in Colombia, since the mid 1990s. I use a measure of radio based on the counting of stations and the exogenous variation in signal transmission given by municipal topographic characteristics to study the effect of the growing number of radio stations on a set of political and policy results. I find that in municipalities with more radio stations turnout for the different types of elections, namely Presidential (1994-2010), Mayor (1994-2011), Senate (1994-2010) and House (1994-2010) elections, increases. I show that the vote share of the winning party in the Senate elections declines and the effective number of parties expands when there is greater exposure to radio, suggesting an increasing electoral competition. Finally, I find that the presence of local media also influences policy. A larger number of radio stations is associated with more resources to investment and a lower share of spending represented by operating expenditures.